Owidiusz i Stacjusz, Tebaida 6.54–78. Aluzje konieczne czy metapoetycki dialog? - Pierzak, Damian (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Statius’ description of the funeral games held in honor of the baby Opheltes contains several utterances reminiscent of Ovid. The paper aims to show that these should not be read as the so-called necessary allusions, but rather as the poet’s complex dialogue with his predecessor.